The prognostic role of combining Krüppel‐like factor 4 score and grade of inflammation in a Norwegian cohort of oral tongue squamous cell carcinomas. (1st April 2022) - Søland, Tine M.; Solhaug, Maren B.; Bjerkli, Inger‐Heidi; Schreurs, Olav; Sapkota, Dipak
Abstract: Krüppel‐like factor 4 (KLF4) is a zinc‐finger transcription factor involved in inflammation, cancer development, and progression. However, the relationship between KLF4, inflammation, and prognosis in oral cancer is not fully understood. KLF4 expression levels were examined in a multicenter cohort of 128 oral squamous cell carcinoma (OSCC) specimens from the tongue (OTSCC) using immunohistochemistry. In two external KLF4 mRNA datasets (The Cancer Genome Atlas/The Genotype‐Tissue Expression Portal), lower KLF4 mRNA expression was found in OSCC and head and neck squamous cell carcinomas (HNSCC) than in control oral epithelium. These data indicate that down‐regulation of KLF4 mRNA is linked to OSCC/HNSCC progression. Using Cox‐multivariate analysis, a significantly favorable 5‐year disease‐specific survival rate was observed for a subgroup of patients with a combination of high levels of KLF4 expression and inflammation. OSCC cell lines exposed to IFN‐γ showed a significant upregulation of nuclear KLF4 expression, indicating a link between inflammation and KLF4 expression in OSCC. Overall, the current data suggest a functional link between KLF4 and inflammation. The combination of high KLF4 nuclear expression and marked/moderate stromal inflammation might be useful as a favorable prognostic marker for a subgroup of OTSCC patients.